AB0927 The Use of Febuxostat in the Treatment of Chronic Severe Gouty Disease. (9th June 2015) - Tan, R.
Abstract : Objectives: Hong Kong with a 7 million population, had 7000 patients on chronic dialysis in the Government Hospitals alone. Many of these patients, up to 25% have a hyperuricemia cause, including acute gouty attacks, tophaceous gout, history of renal stones in their history. The timely, early and sustained lowering of the serum uric acid may lead to fewer chronic cases of renal failure requiring future chronic dialysis. Methods: We followed a group of 60 patients: 48M [31-86; mean 62.35 years]; 12F [49-89; mean 68.67 years] with proven gouty attacks synovial fluid (SF) showing Uric Acid (UA) crystals, or SFUA >5 mg/dl, tophaceous gout, renal stone history and serum (S) UA persistently higher than 7 mg/dl for at least over 2 occasions; placed on long term febuxostat 80 mg OD for 16 months according to ACR guidelines. We monitored their number of acute gouty attacks, renal function, UA, proteinuria to see whether they had fewer acute gouty arthritis, improvement of UA, BUN, Creatinine, and urine protein In the 48M/12F: 14/8 had SF showing: either SFUA crystals on SF analysis or has SFUA >5 mg/dl; 38M/12F had persistently elevated SUA >7 mg/dl (Average for the whole group was 8.26 mg/dl); 15M had tophaceous gout and 7M had history of at least one episode of passing ureteric stone. All the 12F were menopausal. After patients have been placed on Febuxostat for 2 months, SUA were checked, and q4 months. The SUA level was maintained at below 6 mg/dl for all patients throughout the observed period (average for whole group: SUA 5.56 mg/dl) Conclusions: Repeated gouty attacks, tophaceous gout and chronic elevaton of SUA are conditions, if unchecked, will lead to compromised renal function. In the post-menopausal female (usually >50 years) and post-andropausal male (>55 years) age groups, persistent elevated SUA not only will lead to compromised renal function but also lead to increased coronary artery disease (CAD) especially in patients with concomitant DM, hypertension and dyslipidemia singly or in combination. Febuxostat is metabolized through the uridine diphosphate glucuronyltransferase (UDPGT) enzyme system and oxidation via the cytochrome P450 system; it is almost equally metabolized by the kidney (45%) and the liver (45%) and hence dose reduction is not required with compromised liver or kidney function patients. As all of our patients are Chinese, the use of Febuxostat, unlike allopurinol, relieve us of the problem of severe adverse skin reaction such as, Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN.) HLA-5801 allele is a genetic marker for allopurinol-induced severe cutaneous adverse reactions in up to 8% of Han Chinese. In Taiwan, the HLA-5801 is mandatory before allopurinol can be prescribed. We have seen cases of SJS and TEN associated with allopourinol use and this should be avoided. Febuxostat, lowers SUA effectively and relatively and is free of major side effects its liberal use should be encouraged in chinese patients. Disclosure of Interest: None declared